INTERNALISASI NILAI-NILAI PANCASILA DALAM KURIKULUM PRODI PAI FAKULTAS IMU TARTBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR’AN WONOSOBO - salis irvan fuadi; Muhamad Yusuf Amin Nugroho (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
Pancasila is the crystallization of the noble values ​​and culture of the Indonesian nation. In reality, many students in college do not understand it. Using field research, a descriptive approach, the research was concluded: implementation of Pancasila values ​​in the curriculum of the PAI Study Program, Faculty of Tarbiyah and Teacher Training, University of Al-Qur'an Science, Wonosobo, through: (1) written curriculum in the form of academic and non-academic activities, (2) written curriculum: in the form of non-academic activities and habituation.